The prognostic association of triglyceride-glucose index and its derived indicators with stable coronary artery disease patients undergoing percutaneous coronary intervention - Shan, Yu; Lin, Maoning; Gu, Fangfang; Li, Duanbin; Zhu, Qiongjun; Chen, Zhezhe; Zhang, Wenbin; Fu, Guosheng; Wang, Min (Frontiers in Endocrinology, 2025)
AimsResearch on the triglyceride-glucose (TyG) index in patients with stable coronary artery disease (SCAD) remains relatively limited. Therefore, this study aims to investigate the association of the TyG index and its derived indicators, including the baseline TyG index, the baseline triglyceride glucose-body mass index (TyG-BMI), the mean TyG index, and the triglyceride glucose index-standard deviation (TyG-SD), with the prognosis of SCAD patients undergoing percutaneous coronary intervention (PCI).MethodsThis retrospective study enrolled 2,306 patients. The Cox proportional hazards model was utilized to evaluate the association between the four TyG indicators and major adverse cardiovascular and cerebrovascular events (MACCE). The predictive ability of the four TyG indicators for MACCE was assessed using the time-dependent receiver operating characteristic (ROC) curve. Kaplan-Meier survival analysis was employed to assess the prognostic differences among groups.ResultsAfter a median follow-up of 26.1 months, a total of 352 patients (15.3%) experienced MACCE. The Cox regression analysis revealed that under a fully adjusted model, when the four TyG indicators were stratified by tertiles, patients in the highest tertile of each TyG indicator had a significantly increased risk of MACCE compared to those in the lowest tertile. Specifically, the hazard ratio for baseline TyG index was 1.653 (95% confidence intervals (CI): 1.234-2.214), for baseline TyG-BMI was 2.467 (95%CI: 1.849-3.293), for mean TyG index was 2.451 (95%CI: 1.794-3.349), and for TyG-SD was 1.896 (95%CI: 1.430-2.513). Time-dependent ROC curve demonstrated that the mean TyG index had the strongest predictive ability for MACCE at each follow-up time point. The Kaplan-Meier analysis results showed that when the four TyG indicators were grouped by tertiles, there were significant differences in the cumulative incidence of MACCE among the three groups for each indicator (P < 0.05).ConclusionHigher levels of the TyG index and its derived indicators were each independently and positively associated with the risk of MACCE in SCAD patients undergoing PCI. Among these indicators, the mean TyG index demonstrated the greatest predictive value for the risk of MACCE at each follow-up time point. Consequently, tracking the long-term trends of the TyG index may be prioritized in clinical practice.